Rise & Shine Together: Leadership Training to Build Innovative and Collaborative Organizations - Edoardo Tondang; Pralayar Fanny Fadesthi; Muhammad Dika Randi Rawindra; Muhammad Zahwan; Irma Eliyani; Nikita Zahra; Icha Machdita Risma Apriani; Najwa Indira Fitri; Millatus Salamah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The